Menara Worldwide, Bukit Bintang - Muhammad Sabri, Muhammad Rayyan Adam; Nordin, Muhammad Luqman Nurhakim; Nordin, Muhammad Syafiq Aiman; Idrus, Izzul Asuwad (2024)
The capital of the country and largest urban region, Kuala Lumpur serves as the political, economic, and cultural hub of the whole country. It is home to the Parliament of Malaysia, the Istana Negara, which is the official building of the Malaysian King (Yang di-Pertuan Agong). Menara Worldwide is ideally positioned within Kuala Lumpur's Golden Triangle, close to well-known landmarks like Pavilion Shopping Mall, Starhill Gallery, Lot 10, and various five-star hotels. It is situated along Jalan Bukit Bintang, a popular commercial and business district, in the city's center. Menara Worldwide's development in Kuala Lumpur started in the middle of the 1990s, but because of obstacles and the recession brought on by the Asian financial crisis, work on the project was put on hold in July 1999 at the piling and foundation stage Worldwide CEO Norazlina Zakaria tells City & Country. In 2007, Menara Worldwide's construction has resumed after being postponed previously. Worldwide Holdings Bhd made the decision to make improvements to the building’s design and enhance some of the prior plans that were in place for Menara Worldwide and July 2010 declared the completion of the building. Menara Worldwide, in Kuala Lumpur opened for business in 2012. The Sultan of Selangor, Sultan Sharafuddin Idris Shah, officially declared open the Menara Worldwide building in Kuala Lumpur on June 5, 2014.At that time, Dato' Sri Mohd Najib Bin Tun Haji Abdul Razak was Malaysia's prime minister.